Plant regeneration from immature embryo culture of Trifolium michelianum savi. - histological observations on adventitious shoot induction - Robert Konieczny (Acta Societatis Botanicorum Poloniae, 2014)
Whole plant regeneration via organogenesis in immature embryo culture of Trifolium michelianum Savi. was obtained. The shoots were induced directly from the hypocotyl or indirectly through callus on EC6 medium supplemented with 0.5 and 5 mg/l BAP, respectively. Sporadically the callus formation was preceded by shoot regeneration. Both shoots obtained directly and via callus regenerated into plants when subcultured on half-strength Murashige and Skoog (MS) medium, free of growth regulators. Histological observations revealed that the shoots were induced directly from the ring of meristematic tissue which was formed at the periphery of the hypocotyl or indirectly from the superficial cells of the callus. Irrespective of the mode of regeneration the shoots were of multicellular origin.